2006
DOI: 10.1037/1528-3542.6.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Specifying emotional information: Regulation of emotional intensity via executive processes.

Abstract: The degree of specificity at which emotional information is activated might determine evoked emotional intensity. However, the nature of this effect remains unclear. Four studies tested (a) whether people hold the naïve theory that activating specific details of emotional information arouses acute feelings; (b) whether an emotionally distressed population (social phobics) also holds that theory; and (c) whether voluntarily focusing on specific aspects of a distressing situation reduces its emotional impact. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 44 publications
3
42
0
4
Order By: Relevance
“…Additionally, it also increases adaptive rumination, suggesting that both these changes lead to the reduction in symptoms. Our results are also consistent with previous experimental studies indicating that low level of construal processing (as compared to high level) can be changed (e.g., Neumann and Philippot 2007;Philippot et al 2006). Future conceptual formulation of mindfulness should take this into account.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, it also increases adaptive rumination, suggesting that both these changes lead to the reduction in symptoms. Our results are also consistent with previous experimental studies indicating that low level of construal processing (as compared to high level) can be changed (e.g., Neumann and Philippot 2007;Philippot et al 2006). Future conceptual formulation of mindfulness should take this into account.…”
Section: Discussionsupporting
confidence: 92%
“…Congruently, experimental studies have observed that manipulating the level of construal in emotional information processing results in significant variations in emotional regulation (for a review, see Philippot et al 2007). For instance, it has been observed that voluntarily recalling an emotional event in a low-level mode produces less intense emotional responses Philippot et al 2006) and cardiovascular arousal (Schaefer et al 2003) than recalling it at a high-level and abstract mode.…”
Section: Introductionmentioning
confidence: 99%
“…This result replicates recent studies in non-anxious populations and is consistent with other empirical studies that demonstrated a modulation of emotion during the specification of emotional experiences (e.g., Philippot et al, 2003Philippot et al, , 2006Raes et al, 2006). However, there was no significant difference in distress between conditions during the first (rehearsal) exposure session.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a general/generic mode of processing information consists in focusing on features that one repetitively experiences in similar situations, and thus corresponds to a high construal level of thinking. Research has documented that elaborating specific and detailed aspects of episodic emotional information actually reduces distress (e.g., Philippot, Baeyens, & Douilliez, 2006;Philippot, Schaefer, & Herbette, 2003;Raes, Hermans, Williams, & Eelen, 2006). More specifically, several studies have shown that focusing on the unique aspects of a past emotional experience (i.e., those that only occurred during that specific episode), such as its specific contextual elements, reduces emotional intensity.…”
Section: Introductionmentioning
confidence: 99%
“…9 An accurate recognition of experienced emotion facilitate effective regulation of emotions. 10,11 Vulnerability to schizophrenia is heritable to some extent, hence, relatives specifically first-degree relatives are at higher risk of developing psychiatric disorders. 12 The chances of development of schizophrenia in siblings of affected persons are up to 10 times higher than the general population.…”
Section: Introductionmentioning
confidence: 99%